Measles, Mumps, Rubella, and Varicella Zoster Virus Serology and Infections in Solid Organ Transplant Recipients During the First Year Posttransplantation. (21st June 2020) - Rezahosseini, Omid; Sørensen, Søren Schwartz; Perch, Michael; Ekenberg, Christina; Møller, Dina Leth; Knudsen, Andreas Dehlbæk; Kirkby, Nikolai; Lundgren, Jens; Lodding, Isabelle P; Wareham, Neval Ete; Gustafsson, Finn; Rasmussen, Allan; et al.
Abstract: Background: Mumps, measles, rubella, and varicella zoster (MMRV) viruses may cause severe infections in seronegative adult solid organ transplant (SOT) recipients, but can be prevented by vaccination. We aimed to determine MMRV serostatus in adult SOT recipients before and 1 year after transplantation as well as evidence of MMRV infections in a large, prospective cohort of SOT recipients. Methods: This was a prospective study of 1182 adult SOT recipients included in the Management of Posttransplant Infections in Collaborating Hospitals (MATCH) cohort from 2011 to 2017 with a 1-year follow-up. Systematic monitoring of MMRV serology was performed prior to transplantation and 1 year posttransplantation. Polymerase chain reaction (PCR) was used to confirm viral replication in SOT recipients presenting with clinical evidence of infection. Results: Among 1182 adult SOT recipients, 28 (2.4%), 77 (6.5%), 65 (5.5%), and 22 (1.9%) were seronegative for measles, mumps, rubella, and varicella zoster virus (VZV), respectively, and 165 (14%) were seronegative for at least 1 of the MMRV viruses. One year posttransplantation, 29 of 823 (3.5%) of seropositive SOT recipients had seroreverted, and 63 of 111 (57%) of seronegative SOT recipients seroconverted for at least 1 MMRV virus. No evidence of measles, mumps, or rubella infection was found, but 8 (0.7%) SOT recipients developed symptoms and had a positive VZV PCR. Conclusions: A large proportion of SOT recipients were seronegative for at least 1 of the MMRV viruses. MMRV infections in SOT recipients may disseminate and become fatal, and although only a few cases of VZV infection were detected, results from this study suggest increase attention toward vaccination of patients waiting for SOT. Abstract : At the time of transplantation, 14% of adult solid organ transplant recipients were seronegative for at least 1 of measles, mumps, rubella, and varicella zoster viruses, and during the first year posttransplantation, 0.7% had evidence of varicella zoster virus infection.